Cost-effectiveness of remdesivir for the treatment of hospitalized patients with COVID-19: a systematic review - Aziz Rezapour; Zahra Behroozi; Mostafa Nasirzadeh; Mohsen Rezaeian; Mohammad Barzegar; Mahsa Tashakori-Miyanroudi; Abdollah Sayyad; Aghdas Souresrafil (BMC, 2023)
Abstract Background Remdesivir is being studied and used to treat coronavirus disease 2019 (COVID-19). This study aimed to systematically identify, critically evaluate, and summarize the findings of the studies on the cost-effectiveness of remdesivir in the treatment of hospitalized patients with COVID-19. Methods In this systematic review, PubMed, EMBASE, Web of Science, SCOPUS, and the Cochrane Library were searched for studies published between 2019 and 2022. We included all full economic evaluations of remdesivir for the treatment of hospitalized patients with COVID-19. Data were summarized in a structured and narrative manner. Results Out of 616 articles obtained in this literature search, 12 studies were included in the final analysis. The mean score of the Quality of Health Economic Studies (QHES) for the studies was 87.66 (high quality). All studies were conducted in high-income countries (eight studies in the USA and one study in England), except for three studies from middle-to-high-income countries (China, South Africa, and Turkey). Six studies conducted their economic analysis in terms of a health system perspective; five studies conducted their economic analysis from a payer perspective; three studies from the perspective of a health care provider. The results of five studies showed that remdesivir was cost-effective compared to standard treatment. Furthermore, the therapeutic strategy of combining remdesivir with baricitinib was cost-effective compared to remdesivir alone. Conclusions Based on the results of the present study, remdesivir appears to be cost-effective in comparison with the standard of care in China, Turkey, and South Africa. Studies conducted in the United States show conflicting results, and combining remdesivir with baricitinib is cost-effective compared with remdesivir alone. However, the cost-effectiveness of remdesivir in low-income countries remains unknown. Thus, more studies in different countries are required to determine the cost-effectiveness of this drug.